2023
DOI: 10.3390/sym16010028
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Level of Symmetrization of Reaction Time According to Manual Lateralization between Team Sports Athletes, Individual Sports Athletes, and Non-Athletes

Dana Badau,
Adela Badau,
Marko Joksimović
et al.

Abstract: The present study aimed to investigate the impact of practicing sports activities on manual skills, focused on reaction time depending on manual laterality. The objectives of the study were to identify the differences in improving simple, optional, and cognitive reaction times in the manual executions of student athletes who practice team sports involving the manual handling of the ball (volleyball, basketball, handball) in comparison with student athletes who practice individual sports and with non-athletic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 80 publications
2
4
0
Order By: Relevance
“…Our findings reveal that the time elapsed between the onset of a stimulus and the initiation of the response is independent of the hand to be moved, according to the results of multiple comparisons with ANOVA. Given that all participants were right-handed, higher performance in the RT of the dominant hand would have been expected, in line with some previous findings [ 7 , 8 , 17 ]. However, other studies have suggested that this advantage is not generalizable, as it depends on other factors such as target position compatibility [ 35 , 36 ] or free hand choice [ 37 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our findings reveal that the time elapsed between the onset of a stimulus and the initiation of the response is independent of the hand to be moved, according to the results of multiple comparisons with ANOVA. Given that all participants were right-handed, higher performance in the RT of the dominant hand would have been expected, in line with some previous findings [ 7 , 8 , 17 ]. However, other studies have suggested that this advantage is not generalizable, as it depends on other factors such as target position compatibility [ 35 , 36 ] or free hand choice [ 37 ].…”
Section: Discussionsupporting
confidence: 86%
“…Shorter RT was associated with improved performance indicators in both physical capacity and sports skills [ 12 , 13 , 14 , 15 , 16 ]. RT is a key factor in sports performance, influenced by the ability to analyze and decide, as well as the speed of motor responses [ 17 ]. It has been stated that RT can be improved through the implementation of specific training programs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This evolution in training methodologies has the potential to significantly impact the development of young athletes, preparing them more effectively for the demands of competitive sports [53][54][55][56][57]. In accordance with the trends of modernization and technology of sports training, we consider that in order to identify the theoretical and practical methodological aspects, an interdisciplinary approach is necessary in order to improve sports performances [58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research focuses on the identification of symmetry and proportional relationships between different anthropometric body parameters [1][2][3]. A series of studies have highlighted numerous minor asymmetries between different human anthropometric parameters, comparing the morphological development of the right and left side of the body [4,5]. Sports performance is influenced by the individual characteristics of physical development and by the level of the motor and technical ability of athletes in relation to the specifics of the sport practiced [6,7].…”
Section: Introduction 1general Information About Asymmetries In Sportsmentioning
confidence: 99%